Upaya Peningkatan Hasil Belajar Peserta Didik melalui Model Pembelajaran Discovery Learning pada Mata Pelajaran IPA Kelas IX di SMPN 10 Padang - Hafizah, Mufidatul Isnaini; Putri, Rahmah Evita; Yenira, Fitria (Lembaga Yasin AlSys, 2025)
Science learning in class IX.2 at SMPN 10 Padang shows a need to improve student learning outcomes through effective learning methods. This study aims to implement the Discovery Learning model to enhance student learning outcomes in science subjects. The research method used is Classroom Action Research (CAR) involving 32 students during the PPL 2 PPG Teacher Candidate program for the 2024/2025 academic year. The research procedure follows Lewin’s (1992) CAR cycle model consisting of planning, action, observation, and reflection stages across two learning cycles. Data were collected through observation of student learning activities and a 30-item multiple-choice test administered as pretest and posttest, then analyzed using individual mastery percentage formulas. The results showed a significant increase from an average score of 62.81 in cycle I to 75.15 in cycle II, along with an increase in the percentage of students reaching the minimum mastery criteria. Therefore, the Discovery Learning model is effective in improving science learning outcomes for class IX.2 students at SMPN 10 Padang.